Method for preparing nano silicon dioxide by recycling sulfur dioxide

Through the recycling method of sulfur dioxide gas and the use of modifiers, environmental protection problems and performance problems in the preparation of nano-silica are solved, and efficient and economical nano-silica preparation is achieved, which is suitable for the application of a variety of materials.

CN119683636APending Publication Date: 2025-03-25HENAN UNIVERSITY +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411983785.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In the prior art, when preparing nanosilicon dioxide, there are environmental problems, such as the by-product sodium sulfate value, high recycling cost, and the aggregation structure and surface properties of nanosilicon dioxide affect its application performance.

Method used

The sulfur dioxide gas recycling method is used to prepare soluble solid sodium silicate by melting sodium sulfite and quartz sand, and release sulfur dioxide gas for nanosilicon synthesis, and surface modification and structural regulation are used inorganic or organic modifiers during the synthesis process.

Benefits of technology

The recycling of sulfur dioxide is achieved, the production cost is reduced, the dispersion and organic compatibility of nano-silica are improved, and it is suitable for reinforced fillers and modifiers for various materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to a method for preparing nano silicon dioxide by recycling sulfur dioxide. Comprising the following five steps: (1) melting sodium sulfite powder and quartz sand to prepare solid sodium silicate, and releasing sulfur dioxide gas in the process; (2) heating and dissolving solid sodium silicate to obtain water glass; (3) introducing sulfur dioxide gas into the dilute solution of water glass to generate nano silicon dioxide slurry, wherein a byproduct sodium sulfite solution is generated in the process; (4) organically modifying the nano silicon dioxide slurry, filtering and washing, and (5) drying to obtain the modified nano silicon dioxide powder. Wherein the sulfur dioxide gas generated in the step (1) is used for preparing silicon dioxide by hydrolyzing water glass, and the sodium sulfite filtrate obtained by filtering the reaction liquid in the step (3) is dried to obtain sodium sulfite powder which is reused in the step (1). The invention relates to a green and environment-friendly method for preparing nano silicon dioxide by recycling sulfur dioxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of green preparation of nano-silicon dioxide, and particularly relates to a method for preparing nano-silicon dioxide by recycling sulfur dioxide. Background Art

[0002] Industrial processes such as metal smelting and sulfuric acid production generate large amounts of sulfur dioxide gas. Sulfur dioxide is also produced during the combustion of fossil fuels such as coal and oil due to incomplete combustion or reaction with oxygen in the air. Sulfur dioxide emissions pose a significant threat to the environment, such as exacerbating the formation of acid rain, causing water acidification, and damaging aquatic and soil ecosystems. Furthermore, it has potential impacts on human health. Reducing and effectively utilizing sulfur dioxide is crucial for reducing environmental pollution and harm.

[0003] Soluble solid sodium silicate (Na2O·SiO2), produced by fusing quartz sand (SiO2) with alkali, is primarily used as a raw material for the synthesis of white carbon black (nano-sized silica). Alkalis commonly used in quartz sand fusion include sodium hydroxide, sodium carbonate, sodium sulfate, or corresponding potassium salts to lower the melting temperature of the sand. Sodium hydroxide and sodium carbonate are relatively expensive, making the production of sodium sulfate more costly. Sodium sulfate, while less expensive, releases sulfur dioxide during fusion, leading to the sodium sulfate method being designated as a restricted development method by the government. The basic process for producing white carbon black involves dissolving solid sodium silicate in water under heating and pressure to form water glass. The water glass is then diluted with water to a certain concentration, and an inorganic acid is added to form a sol, which then grows into nano-silica particles. Further aging occurs to form a specific aggregate structure. Commonly used inorganic acids include hydrochloric acid and sulfuric acid, generating corresponding sodium salts such as sodium chloride and sodium sulfate as byproducts. Sodium chloride is highly corrosive to equipment, while sodium sulfate has a low value and high recovery costs, making it a persistent environmental challenge in the industry. At the same time, the aggregate structure and surface properties of nano-silica particles determine their application performance. Silica produced by liquid-phase methods, especially precipitation methods, often exists in agglomerated form, severely reducing its nano-properties. Therefore, the industry urgently needs to research and develop environmentally friendly, cost-effective, and high-performance silica (nano-silica) production technologies.

[0004] Based on this, this application was developed. Summary of the Invention

[0005] The present invention aims to overcome the shortcomings of the prior art by providing a method for preparing nano-silica by recycling sulfur dioxide. The core of this method is to use sulfur dioxide, instead of traditional sulfuric acid or hydrochloric acid, to react with sodium silicate, generating sodium sulfite as a byproduct while preparing silica. The sodium sulfite is then melted with quartz sand to prepare sodium silicate, and the sulfur dioxide gas released during the process is then used in the synthesis of silica, thereby achieving the recycling of sulfur dioxide to prepare nano-silica. Inorganic / organic modifiers are used to modify the surface and regulate the structure of the nano-silica, resulting in functional nano-silica with good dispersibility.

[0006] To achieve the above object, the technical solution adopted by the present invention is as follows: A method for preparing nano-silicon dioxide by recycling sulfur dioxide (the process flow chart is as follows Figure 5 ), which includes the following steps: 1) Sodium sulfite powder is melted and reacted with quartz sand to produce soluble solid sodium silicate (sodium silicate), which releases sulfur dioxide gas. 2) heating and dissolving the solid sodium silicate obtained in step 1) to obtain water glass; adding water to dilute the water glass to form a dilute sodium silicate solution; 3) introducing the sulfur dioxide gas obtained in step 1) into the dilute sodium silicate solution obtained in step 2) to react and generate a nano-silicon dioxide slurry, wherein a sodium sulfite solution is generated as a by-product; filtering and washing the nano-silicon dioxide slurry, and adding a modifier to the filter cake to perform a modification reaction after the reaction is completed, and drying to obtain the product; Alternatively, the sulfur dioxide gas obtained in step 1) is introduced into the dilute sodium silicate solution obtained in step 2) and a modifier is added to react. The reaction conditions are the same as those for producing the nano-silicon dioxide slurry. This process produces a sodium sulfite solution as a by-product. After the reaction is completed, the mixture is filtered, washed, and dried to obtain the product.

[0007] Specifically, the sodium sulfite solution produced as a byproduct in step 3) is dried to obtain sodium sulfite powder, which is then recycled as the raw material for step 1). In the method of the present invention, the sulfur dioxide gas produced in step 1) is used to hydrolyze water glass to produce silicon dioxide. The sodium sulfite filtrate obtained by filtering the reaction solution in step 3) is then dried to obtain sodium sulfite powder, which is then reused as the raw material for step 1). This invention provides a green and environmentally friendly method for producing nano-silicon dioxide by recycling sulfur dioxide.

[0008] Furthermore, in step 1), the molar ratio of sodium sulfite powder to quartz sand is 1:2.3-1:3.5, and the melting temperature is 1000-1400°C.

[0009] Specifically, in step 2), during the process of heating and dissolving solid sodium silicate to obtain water glass, the water glass has a solid content of 30% to 43%, a dissolution temperature of 150 to 170°C, and a dissolution pressure of 5 to 8 MPa. Heating can be performed using superheated steam or electric heating. The water glass is diluted with water to form a dilute sodium silicate solution having a solid content of 4 to 18%.

[0010] Specifically, in step 3), sulfur dioxide gas is introduced into a dilute sodium silicate solution to react and generate a nano-silica slurry; or sulfur dioxide gas is introduced into water to prepare a sulfurous acid solution, which is then added to a dilute sodium silicate solution to react and generate a nano-silica slurry; the reaction is carried out at normal pressure or a medium-low pressure of 0.1-0.8 MPa, a reaction temperature of 30-170° C., and a reaction time of 1-12 hours.

[0011] Furthermore, in step 3), sulfur dioxide gas is introduced until the system pH is 3-10. In this pH range, the molar ratio of sodium oxide in the water glass to sulfur dioxide gas is controlled to be 1:0.8-1:1.5.

[0012] There are two methods for modifying, filtering, and washing the nanosilica slurry in step 3). One is to add the modifier directly to the synthesis process for modification, followed by filtering and washing. The other is to filter and wash the nanosilica slurry first, slurry the filter cake, and then add the modifier for modification. Alternatively, the modifier can be added in stages, initially adding a small amount, followed by a predetermined amount after the sulfur dioxide gas is introduced. Organic and / or inorganic modifiers can be added during the reaction. Preferably, in step 3), the modifier includes inorganic and / or organic modifiers. Inorganic modifiers include decomposable inorganic salts such as one or more of sodium bicarbonate, ammonium sulfate, ammonium bicarbonate, and urea. Organic modifiers include one or more of organosilicones such as silane coupling agents, chlorosilanes, silazanes, and polydimethylsiloxanes, as well as organic acids. More preferably, the amount of the modifier added is 3-30% of the mass of the nano-silica; the temperature of the modification reaction is 30-90° C.; and the time of the modification reaction is 0.5-5 hours.

[0013] Furthermore, in step 3), the reaction slurry can be filtered and washed using a plate and frame filter press or a ceramic membrane filter until the filtrate conductivity reaches below 500 μs / m. Drying can be performed using spray drying or flash drying, with an inlet temperature of 300-700°C and an outlet temperature of 70-140°C; alternatively, drying can be performed using a fluidized bed or oven drying, with a drying temperature of 100-250°C.

[0014] Specifically, the sulfite filtrate produced by filtration and washing in step 3) can be concentrated and evaporated in combination with multiple-effect evaporation or MVR evaporation to obtain solid sodium sulfite. The obtained solid sodium sulfite is recycled to step (1), mixed with quartz sand and melted to prepare solid sodium silicate. The sulfur dioxide gas released during the melting reaction is recovered and used to prepare the nano-silicon dioxide slurry in step 3), thereby realizing the recycling of sulfur dioxide. If modified with inorganic salts, the sodium sulfite may contain a small amount of carbonate or sulfate, which does not affect its recycling.

[0015] The present invention discloses a method for preparing nano-silicon dioxide by recycling sulfur dioxide, comprising: melting sodium sulfite powder and quartz sand to prepare soluble solid sodium silicate, while simultaneously releasing sulfur dioxide gas; heating and dissolving the solid sodium silicate in water to obtain water glass; diluting the water glass with water to form a dilute sodium silicate solution; introducing the released sulfur dioxide gas into the solution to generate sodium sulfite, which reacts with the sodium silicate to produce a nano-silicon dioxide slurry while simultaneously performing in-situ surface modification; filtering and washing the slurry after the reaction, and drying the filter cake to obtain a modified nano-silicon dioxide powder product; drying the byproduct sodium sulfite contained in the filtrate to obtain sodium sulfite powder, which is reused for melting quartz sand. During the preparation process, sulfur dioxide can be introduced into a sodium silicate aqueous solution, or sulfur dioxide gas can be introduced directly into water, where the sulfur dioxide and water generate sulfurous acid; the sodium silicate reacts with the sulfurous acid, and as the pH value of the solution decreases, the sodium silicate generates a sol, which is then converted into nano-silicon dioxide particles, which are then aged to form aggregates with a certain structure.

[0016] The present invention prepares nano-silicon dioxide by introducing sulfur dioxide gas into a sodium silicate aqueous solution, and utilizes the generated by-product sodium sulfite to fuse with quartz sand to prepare solid sodium silicate, thereby realizing the recycling of the released sulfur dioxide gas. Simultaneously, during the synthesis of the nano-silicon dioxide, inorganic or organic modifiers are used for in-situ surface modification and structural regulation, thereby obtaining highly dispersible and multifunctional nano-silicon dioxide (white carbon black).

[0017] Compared with the prior art, the present invention has the following beneficial effects: 1) The present invention uses sulfur dioxide gas to pass into a sodium silicate aqueous solution to prepare nano-silicon dioxide, and utilizes the by-product sodium sulfite to fuse with quartz sand to prepare solid sodium silicate. This is a green method for synthesizing silicon dioxide and its raw materials.

[0018] 2) In the process of synthesizing the nano-silica of the present invention, inorganic or organic modifiers are used for surface modification and structural regulation, which can achieve structural regulation of the nano-silica and significantly improve its dispersibility and organic compatibility. It can be used as a reinforcing filler and modifier for (silicone) rubber, coatings, inks, thermal insulation materials, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1This is a transmission electron microscope photo of the nano-silica prepared in Example 1. The results show that the nano-silica has a highly developed network structure and the original particle size is 5-10nm; Figure 2 This is a transmission electron microscope photo of the nano-silica prepared in Example 2. The results show that the nano-silica has a network structure and an original particle size of about 20 nm. Figure 3 This is a transmission electron microscope photo of the nano-silica prepared in Example 3. The results show that the nano-silica has a macroporous branched structure and an original particle size of 5-10 nm. Figure 4 This is a transmission electron microscope photo of the nano-silica prepared in Example 4. The results show that the nano-silica has a stacked structure and the original particle size is about 20nm; Figure 5 It is a process flow chart of the preparation method of the present invention. DETAILED DESCRIPTION

[0020] The technical solution of the present invention is further described in detail below in conjunction with the embodiments, but the protection scope of the present invention is not limited thereto.

[0021] In the following examples, unless otherwise specified, the raw materials used are common commercial products that can be purchased directly, or can be prepared using conventional methods in the art.

[0022] Preparation of raw materials sodium silicate and sodium silicate: 1. Preparation of soluble solid sodium silicate: quartz sand and sodium sulfite are melted at a molar ratio of 2.4-3.5:1 to obtain soluble solid sodium silicate (i.e., sodium silicate) with a modulus of 2.4-3.5. The sodium sulfite is a byproduct of the nano-silica synthesis reaction in the examples.

[0023] 2. Preparation of Water Glass: For economic reasons, high-modulus sodium silicate is preferred. Solid sodium silicate with a modulus of 2.8-3.5 is dissolved in water at a temperature of 150-170°C and a pressure of 5-8 MPa. The resulting water glass has a solid content of 30%-43%. Sodium hydroxide can also be used to adjust the modulus, allowing it to be adjusted within the range of 1.0-3.5.

[0024] 1) Taking sodium silicate with a modulus of 3.06 and a silicon dioxide content of 24.6% as an example, it is prepared by the following steps: Sodium sulfite powder and quartz sand are melted and mixed in a molar ratio of 1:3.06, and then heated to 1400°C for melting to prepare a soluble solid sodium silicate (also known as sodium silicate, with a silicon dioxide content of 24.6%) with a modulus of 3.06. This process releases sulfur dioxide gas.

[0025] The prepared sodium silicate with a modulus of 3.06 was added with water to prepare water glass with a concentration of 32.9%. The dissolution temperature was 160°C and the pressure was 6.5 MPa. Water glass with a solid content of 32.9%, a modulus of 3.06, a silicon dioxide content of 24.6%, and a sodium oxide content of 8.3% was prepared.

[0026] 2) Taking sodium silicate with a modulus of 2.8 and a silicon dioxide content of 25.0% as an example, it is prepared by the following steps: Sodium sulfite powder and quartz sand are melted and mixed in a molar ratio of 1:2.8, and then heated to 1280°C for melting to prepare a soluble solid sodium silicate (i.e., sodium silicate, with a silicon dioxide content of 25.0%) with a modulus of 2.8. This process releases sulfur dioxide gas.

[0027] The prepared sodium silicate with a modulus of 2.8 was added with water to prepare water glass with a concentration of 34.23%. The dissolution temperature was 150°C and the pressure was 6.0 MPa. Water glass with a solid content of 34.23%, a modulus of 2.8, a silicon dioxide content of 25.0%, and a sodium oxide content of 9.23% was prepared.

[0028] In the following examples, water glasses with different solid contents prepared by the above method were used, and modified nano-silica was prepared using sulfur dioxide gas collected during the above melting process as a raw material (the insufficient amount was supplemented by purchased sulfur dioxide gas).

[0029] Example 1 Synthesis of highly dispersed nano-silicon dioxide 76g of water glass (solids content, 32.9%) with a modulus of 3.06 and a silica content of 24.6% was added to a reaction flask. 324g of pure water was added, and the temperature was raised to 40°C. SO2 gas was introduced until the pH reached 9-10. The reaction was then heated to 60°C for 1 hour and then to 80°C for 2 hours to produce a nano-silica slurry. This process also produced a sodium sulfite solution as a byproduct. The reaction slurry was filtered and washed until the conductivity of the filtrate was below 300μs / m. Water was added to the filter cake to a silica concentration of 8% and the mixture was stirred thoroughly. 0.06g of urea (3‰ by weight of the silica) and 1.5g of KH-550 (8% by weight of the silica) were added as a modifier and the mixture was reacted at 90°C for 2 hours. After the reaction, the mixture was filtered and spray-dried, with the inlet temperature controlled between 400-440°C and the outlet temperature between 105-120°C, to obtain hydrophobic nano-silica powder. The product has an original particle size of 5~10nm, a specific surface area of ​​364㎡ / g, and excellent organic dispersibility.

[0030] Example 2 Synthesis of Double-bonded Nanosilica 96g of water glass (solids content, 34.23%) with a modulus of 2.8 and a silica content of 25.0% was added to a hydrothermal reactor. 304g of pure water was added, and the temperature was raised to 130°C. SO2 gas was introduced until the pH reached 5-6, and the reaction was allowed to proceed for 1 hour to produce a nano-silica slurry. This process also produced a sodium sulfite solution as a byproduct. The reaction slurry was filtered and washed until the conductivity of the filtrate was below 300μs / m. Water was added to the filter cake to a silica concentration of 10%, and the mixture was stirred thoroughly. 3g of silane coupling agent KH-570g (12.5% ​​by weight of the silica) was added, and the reaction was continued at 80°C for 3 hours. After the reaction, the mixture was filtered and spray-dried, maintaining the inlet temperature between 320-340°C and the outlet temperature between 95-120°C, to obtain hydrophobic nano-silica powder with double bonds. The product had an initial particle size of approximately 20nm, exhibited hydrophobicity, and a specific surface area of ​​267 m2 / g.

[0031] Example 3 Synthesis of highly branched nanosilica 76g of water glass (solids content, 32.9%) with a modulus of 3.06 and a silica content of 24.6% was added to a hydrothermal reactor. 324g of pure water and 0.09g of ammonium bicarbonate (5‰ by weight of the silica) were added as a modifier. The reaction was heated to 40°C, and SO2 gas was introduced until the pH reached 8-9. 3g of polydimethylsiloxane (16% by weight of the silica) was added as a modifier. The reaction was continued at 80°C for 2 hours. After the reaction, the mixture was filtered and washed until the filtrate's conductivity fell below 150μs / m. The filter cake was flash dried at a controlled inlet temperature of 370-390°C and an outlet temperature of 105-115°C to obtain highly branched nanosilica powder with an initial particle size of 5-10nm and a specific surface area of ​​344㎡ / g.

[0032] Example 4 Synthesis of super-hydrophobic nano-silica 130g of water glass (solids content, 32.9%) with a modulus of 3.06 and a silica content of 24.6% was added to a reaction flask. 270g of pure water was added, and the temperature was raised to 60°C. SO2 gas was introduced until the pH reached 4-5. The reaction was then heated to 150°C for 1 hour to produce a nano-silica slurry. This process also produced a sodium sulfite solution as a byproduct. The reaction slurry was filtered and washed until the conductivity of the filtrate was below 300μs / m. Water was added to the filter cake to a silica concentration of 8%, and the mixture was stirred thoroughly. 4.8g of hexamethyldisilazane (15% by weight of the silica) was added as a modifier, and the mixture was reacted at 60°C for 1 hour and 80°C for 2 hours. After the reaction, the mixture was filtered and spray-dried, with the inlet temperature controlled between 400-440°C and the outlet temperature between 115-130°C, to obtain superhydrophobic nano-silica powder. The original particle size of the product is about 20nm, the specific surface area is 120㎡ / g, and it has super hydrophobicity and organophilicity.

[0033] The sodium sulfite solution produced as a by-product during the preparation process of the above embodiment is dried to obtain sodium sulfite powder, which is reused as a raw material for melting reaction with quartz sand to prepare soluble solid sodium silicate.

[0034] Figure 1 The transmission electron microscope photograph of the nano-silica prepared in Example 1 is given. The results show that the nano-silica has a highly developed network structure and an original particle size of 5-10 nm.

[0035] Figure 2 The transmission electron microscope photograph of the nano-silica prepared in Example 2 is given, and the results show that the nano-silica has a network structure and an original particle size of about 20 nm.

[0036] Figure 3 The transmission electron microscope photograph of the nano-silica prepared in Example 3 is given. The results show that the nano-silica has a macroporous branched structure and an original particle size of 5-10 nm.

[0037] Figure 4 A transmission electron microscope photograph of the nano-silica prepared in Example 4 is given. The results show that the nano-silica has a stacked structure and an original particle size of about 20 nm.

[0038] Table 1 Quality indicators of nano-silicon dioxide prepared under the conditions of each example Table 1 shows the quality indicators of the nano-silica prepared under the conditions of each example. As can be seen from the table, the nano-silica prepared by the present invention has excellent dispersibility and can be used as a reinforcing material for rubber, a thixotropic agent and defoaming agent for coatings, and a thermal insulation material, etc., and has a wide range of application prospects.

Claims

1. A method for preparing nano-silicon dioxide by recycling sulfur dioxide, characterized in that: The steps include: 1) Sodium sulfite powder is melted and reacted with quartz sand to prepare solid sodium silicate, which releases sulfur dioxide gas; 2) heating and dissolving the solid sodium silicate obtained in step 1) to obtain water glass; further diluting with water to form a dilute sodium silicate solution; 3) introducing the sulfur dioxide gas obtained in step 1) into the sodium silicate dilute solution obtained in step 2) to react and generate nano-silicon dioxide slurry, and in this process, a sodium sulfite solution is generated as a byproduct; filtering and washing the nano-silicon dioxide slurry, adding a modifier to the filter cake slurry for modification reaction, and drying after the reaction is completed to obtain the nano-silicon dioxide slurry; Alternatively, the sulfur dioxide gas obtained in step 1) is introduced into the sodium silicate dilute solution obtained in step 2) and a modifier is added to react. The reaction conditions are the same as those for generating the nano-silicon dioxide slurry. This process generates a sodium sulfite solution as a by-product. After the reaction is completed, the modified nano-silicon dioxide powder is obtained by filtering, washing and drying.

2. The method for preparing nano silicon dioxide by recycling sulfur dioxide as claimed in claim 1, characterized in that: Step 3) The byproduct sodium sulfite solution is dried to obtain sodium sulfite powder, which is recycled as the raw material of step 1).

3. The method for preparing nano silicon dioxide by recycling sulfur dioxide as claimed in claim 1, characterized in that: In step 1), the molar ratio of sodium sulfite powder to quartz sand is 1:2.3-1:3.5, and the melting temperature is 1000-1400°C.

4. The method for preparing nano silicon dioxide by recycling sulfur dioxide as claimed in claim 1, characterized in that: In step 2), during the process of heating and dissolving solid sodium silicate to obtain water glass, the solid content of the water glass is 30% to 43%, the dissolution temperature is 150 to 170° C., and the dissolution pressure is 5 to 8 MPa; the water glass is diluted with water to form a dilute sodium silicate solution, and the solid content of the solution is 4 to 18%.

5. The method for preparing nano silicon dioxide by recycling sulfur dioxide as claimed in claim 1, characterized in that: In step 3), sulfur dioxide gas is introduced into a dilute sodium silicate solution to react and generate a nano-silicon dioxide slurry; or sulfur dioxide gas is introduced into water to prepare a sulfurous acid solution, which is then added into a dilute sodium silicate solution to react and generate a nano-silicon dioxide slurry; the reaction is carried out at normal pressure or at a medium-low pressure of 0.1-0.8 MPa, at a reaction temperature of 30-170° C., and for a reaction time of 1-12 hours.

6. The method for preparing nano-silicon dioxide by recycling sulfur dioxide as claimed in claim 5, characterized in that: In step 3), sulfur dioxide gas is introduced until the pH of the system is between 3 and 10.

7. The method for preparing nano-silicon dioxide by recycling sulfur dioxide as claimed in claim 5, characterized in that: In step 3), the modifier includes an inorganic modifier and / or an organic modifier, the inorganic modifier includes one or more of sodium bicarbonate, ammonium sulfate, ammonium bicarbonate and urea, and the organic modifier includes one or more of a silane coupling agent, chlorosilane, silazane, polydimethylsiloxane and an organic acid.

8. The method for preparing nano-silicon dioxide by recycling sulfur dioxide as claimed in claim 7, characterized in that: In step 3), the amount of the modifier added is 3-30% of the mass of the silicon dioxide in the reaction solution; the temperature of the modification reaction is 30-90° C., and the time of the modification reaction is 0.5-5 hours.

9. The method for preparing nano silicon dioxide by recycling sulfur dioxide as claimed in claim 1, characterized in that: In step 3), washing is performed until the conductivity of the filtrate reaches below 500 μs / m.

10. The method for preparing nano-silicon dioxide by recycling sulfur dioxide as claimed in claim 1, characterized in that: In step 3), the drying is carried out by spray drying or flash drying, with an inlet temperature of 300-700°C and an outlet temperature of 70-140°C; or the drying is carried out by fluidized bed or oven drying, with a drying temperature of 100-250°C.